Effects of Past Burning Frequency on Woody Plant Structure and Composition in Dry Dipterocarp Forest - Wanthongchai, Kobsak; Bauhus, Jürgen; G. Goldammer, Johann (วารสารวนศาสตร์ไทย, 2022)
Anthropogenic burning in dry dipterocarp forests has become a common phenomenon throughout Thailand. Too frequent fires may affect plant species composition, soil properties and processes, and nutrient dynamics, thereby impacting upon ecosystem productivity and sustainability. Conversely, complete fire exclusion, may result in changes to ecosystem components, and an increased risk of high-intensity wildfire. This study aimed to investigate the effects of different burning histories (7, 2, 1 or 0 fires in the past 10 years) and prescribed fire on sites with different past burning regimes on woody plant structure and composition in a dry dipterocarp forest at Huai Kha Khaeng Wildlife Sanctuary, Thailand. Each burning history comprised of three 30m×30m plots for the measurement of overstorey vegetation. Four 4m×4m subplots were set up within the plot to assess saplings and seedlings. These investigations were measured both pre-burn and one-year post-burn. The study revealed that the structure of stands that had been frequently burned in the past differed from that of the less frequently burned stands. Moreover, the species composition of the small-sized overstorey vegetation in the frequently burned stands also differed significantly from that of the other stands. The species composition of the unburned site differed from that of the other burning regimes only modestly. Frequent burning also resulted in a reduction of the sprouting capacity of seedlings and saplings, inhibited regeneration and, consequently, resulted in a disproportionate representation of individuals of certain tree species at the various stages of development. Therefore, fire-free intervals of at least 6-7 years should be introduced to facilitate the successful recruitment of young trees. Keywords: Burning frequency, Dry dipterocarp forest, Huai Kha Khaeng Wildlife Sanctuary, Prescribed fire, Woody plant